Meet Curious George : a picture reader - Huelin, Jodi.; Kaufman, Kenneth; Reynolds, David; Rey, Margret; Rey, H. A. (Hans Augusto), 1898- ([Boston, Mass.] : Houghton Mifflin Co., 2005)
George has lots of fun living in his jungle home. Then one day he meets a man in a yellow hat and decides to follow him out of the jungle and onto a big ship. When the ship sails away, George goes with it and into a big adventure.
"Curious George, the movie."
Based on the motion picture story by Ken Kaufman ; motion picture screenplay by Ken Kaufman and David Reynolds ; based on the books by Margret and H.A. Rey.
Keywords: Curious George (Fictitious character) -- Juvenile fiction; Monkeys -- Juvenile fiction; Monkeys -- Fiction